2022
DOI: 10.1002/joom.1205
|View full text |Cite
|
Sign up to set email alerts
|

Global buyer–supplier networks and innovation: The role of technological distance and technological breadth

Abstract: One of the critical challenges of technology management for a firm is managing technological knowledge. This study focuses on available technological knowledge in a firm's global supplier network and examines factors that accrue innovation benefits from such knowledge for a buyer firm. Using absorptive capacity as a theoretical lens, we specifically examine technological distance, technological breadth, and extent of global sourcing, and how these factors interrelate in influencing a firm's innovation performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Specifically, we verified this possibility by using the two‐stage residual inclusion approach, also known as the control function approach (Wooldridge, 2015). This approach is particularly appropriate for nonlinear regression models including count data models, which are often utilized in recent supply chain management (SCM) research (e.g., Liu et al, 2021; Palit et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we verified this possibility by using the two‐stage residual inclusion approach, also known as the control function approach (Wooldridge, 2015). This approach is particularly appropriate for nonlinear regression models including count data models, which are often utilized in recent supply chain management (SCM) research (e.g., Liu et al, 2021; Palit et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The value assigned to focal firms exceeding the median value of tier-1 suppliers in the sample is 1, otherwise it is 0, which represents the relative level of the in-degree centrality (Similar variable processing approach can refer to (Lee et al. , 2020; Palit et al. , 2022)). Out-degree Centrality (OC) : This variable corresponds to H5.…”
Section: Methodsmentioning
confidence: 99%
“…Considering that the number of tier-1 suppliers is highly real-time data and depends on relationship disclosure, we believe that small differences in the number of tier-1 suppliers may not be meaningful, so we convert in-degree centrality into a binary variable. The value assigned to focal firms exceeding the median value of tier-1 suppliers in the sample is 1, otherwise it is 0, which represents the relative level of the in-degree centrality (Similar variable processing approach can refer to (Lee et al, 2020;Palit et al, 2022)).…”
Section: Smart Supply Chain and Stock Market Reactionmentioning
confidence: 99%
“…Phene et al (2006) indicated a nonlinear relationship between technologically distant knowledge of national origin and breakthrough innovation, while technologically proximate knowledge of international origin has a positive impact on breakthrough innovation. In the study on global buyer-supplier networks and innovation, Palit et al (2022) pointed out that technological distance can pose challenges in recombining knowledge and have a negative impact on innovation performance. Capaldo et al (2017) studied the relationship between technological distance and knowledge maturity, arguing that technological distance reduces the benefits of knowledge maturity because limited familiarity undermines the reliable use of mature knowledge while making it more difficult to retrieve and apply.…”
Section: Technological Boundary Spanning Searchmentioning
confidence: 99%
“…(2006) indicated a nonlinear relationship between technologically distant knowledge of national origin and breakthrough innovation, while technologically proximate knowledge of international origin has a positive impact on breakthrough innovation. In the study on global buyer-supplier networks and innovation, Palit et al. (2022) pointed out that technological distance can pose challenges in recombining knowledge and have a negative impact on innovation performance.…”
Section: Introductionmentioning
confidence: 99%